Sex ratios and missing girls in late-19th-century Europe - Francisco J. Beltrán Tapia (European Historical Economics Society (EHES), 2019)
This paper reconstructs infant and child sex ratios, the number of boys per hundred girls, in Europe circa 1880. Contrary to previous interpretations arguing that there is little evidence of gender discrimination resulting in excess female mortality in infancy and childhood, the results suggest that this issue was much more important than previously thought, especially in Southern Europe. The unbalanced sex ratios observed in some regions are not due to random noise, female miss-reporting or sex-specific migration. Likewise, although geography, climate and population density influenced sex ratios, these factors cannot explain away the patterns of gender discrimination reported here. The actual nature of discrimination, either female infanticide, the abandonment of young girls and/or the unequal allocation of resources within families, however, remains unclear and surely varied by region.
Keywords: I14; I15; J13; J16; N33; 330; Sex ratios; Infant and child mortality; Gender discrimination; Health